Marital rape in Malaysia: a discourse on human rights perspective - Mohd Bajury, Mimi Sintia; Salleh, Fauzilah; Abdullah, Kamarulnizam; Md Dahlan, Nuarrual Hilal; Abdullah, Berhanundin; El-Muhammady, Ahmad; Roslam, Aini Fatihah; Muhammad Aziz, Mohd Iskandar (nstitute of Public Security of Malaysia (IPSOM) Ministry of Home Affairs, 2023)
Historically, marital rape has not been recognized as a criminal act. Up until now, the majority of countries in the world do not have laws specifically prohibiting sexual assault during matrimony also known as marital rape. While sexual assault, in general, is being criminalized everywhere in the According to a study conducted by University Sains Malaysia (USM) in 2014, nine out of every ten Peninsular Malaysian women who have ever been in a relationship had experienced domestic violence at some point in their lives. 11% of these women have also reported being subjected to "forced sex" as a form of abuse. To date, there are no laws in Malaysia specifically prohibiting marital rape. While section 375A has been included as an amendment to the Penal Code, it is insufficient to remedy the gap in the law. It is imperative that marital rape be made a crime as soon as possible. Not only it is a problem in Malaysia, nevertheless, a review of international law and human rights standards indicates that countries that do not promulgate marital sexual assault illegal, are in violation of both the due diligence requirement and the international human rights standards. The extent of the unfinished business in the field of human rights law is demonstrated by the notable legal gaps that still exist throughout the world, providing legal immunity to men who violate their intimate partners. Given that marriage is the cornerstone of Malaysian society, marital rape should be a cause for concern because it would increase a host of other societal problems.